2020
DOI: 10.47203/ijch.2020.v32i04.014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of one-day training on Knowledge related to Biosafety and waste management among life-science Students

Abstract: Context: Laboratory workers are at increased risk of occupational hazards especially microbial infections. These occupational hazards can be reduced by merely creating awareness related to Biosafety. Thus biosafety and waste management training is important and needs to be inculcated at novice stage. Aims: The present study aimed to assess the effect of one-day training program on knowledge related to biosafety and biohazard among life-science students. Settings and Design: The study was conducted through onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
2
0
1
Order By: Relevance
“…Similar anticipated results i.e. knowledge enhancement using the ECHO model, have been realised earlier through comparable studies [7,8]. An Indian study reported an increase in average knowledge level score of 14.4 from the baseline score of 6.3, after the ECHO training 6 months post the initial 3-day in-person training on oral, breast, and cervical cancer screening of HCPs in the tribal primary healthcare centre of Gumballi [9].…”
Section: Discussionsupporting
confidence: 82%
“…Similar anticipated results i.e. knowledge enhancement using the ECHO model, have been realised earlier through comparable studies [7,8]. An Indian study reported an increase in average knowledge level score of 14.4 from the baseline score of 6.3, after the ECHO training 6 months post the initial 3-day in-person training on oral, breast, and cervical cancer screening of HCPs in the tribal primary healthcare centre of Gumballi [9].…”
Section: Discussionsupporting
confidence: 82%
“…A validação de um instrumento único que pode ser aplicado no ensino e no cotidiano dos serviços de saúde poderá contribuir para maior consistência na adesão aos aspectos de biossegurança na prática. Além disso, envolver profissionais e estudantes na avaliação da utilização do checklist aponta para a necessidade e importância da biossegurança como tema da educação permanente e da formação dos profissionais de saúde (18,19) . O uso de um podem ser assistidas na atenção primária (20) , secundária (21) ou terciária (22) ; o que aponta para a necessidade de capacitação ampla a todos aqueles que assistem direta ou indiretamente as pessoas nesses serviços.…”
Section: Discussionunclassified
“…Training of healthcare workers is important as it has resulted in improvement of their clinical practices as well as patient outcomes by increasing their clinical knowledge [10,17].…”
Section: Discussionmentioning
confidence: 99%